Effect of Blowing Agent to the Dielectric Properties of Polyurethane-Empty Fruit Bunch Composite in X-Band Frequency - Syarifah Norsuhaila, Syed Mahmud; Mohamad Ashry, Jusoh; You, Kok Yeow; Fahmiruddin, Esa (Trans Tech Publications, 2020)
Nowadays, the usage of blowing agent in polyurethane preparation has been an essential enhance the characterization of polymers or composites material. The use of blowing agent may affect the properties of the materials and directly alter the performance of resulting product. In this paper, the effect of a blowing agent on dielectric properties of palm oil-based polyurethane (POlyOP) have been studied. The palm oil-based polyurethane ( POlyOP) has been prepared using the presence of water act as a blowing agent and tegostab 8486 act as a surfactant. The Oil Palm Empty Fruit Bunch (EFB) was used in the composite as filler. The dielectric constant and loss factor analysis in this study was carried out by Vector Network Analyzer (VNA) at x-band frequency using Nicholson-Ross-Weir (NRW) technique. The dielectric study of PolyOP composite showed that the presence of blowing agent in composite enhance the value of dielectric properties of composite at x-band frequencies